A Multicenter Initiative for Critical Congenital Heart Disease Newborn Screening in Texas Neonatal Intensive Care Units - Gong, Alice; Guillory, Charleta; Creel, Liza; Livingtson, Judith Ellen; McKee-Garrett, Tiffany M.; Fortunov, Regine (American Journal of Perinatology, 2017)
Objective The objective of this study was to implement a strategy for critical congenital heart disease (CCHD) newborn screening in the neonatal intensive care unit (NICU).Design A NICU-specific curriculum, screening algorithm, slide presentations, and templates of orders, policies, and procedures were developed into a toolkit for training NICU personnel. Screening was conducted on first and second screen pre- and postductal oxygen saturations (SpO2) on newborns admitted or transferred to the NICU.Results We trained 347 NICU personnel in 13 Texas hospitals, representing rural, suburban, and metropolitan settings. Key hospital staff submitted deidentified, case-based screening data. Of 4,621 NICU admissions, 80% received a first screen. Second screening rates were substantially lower in all gestational age groups. Screening rates on first and second screens were lowest among infants born < 28 weeks. For the first screen, SpO2 was lowest among the youngest gestational ages. The false positive rate was 2.3%.Conclusion CCHD screening in the NICU is challenging, given the complexities of the NICU population. A modified screening protocol that recognizes special circumstances of neonatal intensive care could facilitate a more efficient system.
Keywords: critical congenital heart disease; NICU; newborn screening; multicenter